Löftesrika ringar - Knuts, Eva (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
Wedding rings have strong networks of actors that want them to circulate in wedding rituals, on market places and in human minds. Rings are seen as a "natural" part of wedding ceremonies but are not needed when you get married. Wedding rings are artefacts that get a lot of attention in wedding magazines and hold a strong position at the moment. Wedding rings help to stabilize relations, subjects and the wedding ritual. This object externalizes values which are embedded in social processes and makes it visible and negotiable but it is also an object with materiality. The wedding ritual becomes more legible with material objects and the objects get a deeper meaning through the ritual, a "win-win" situation.